Foreign Exchange Market Liquidity and Currency Rate: A Causality Approach - Onyendi, Hilary Uchenna (Social Science Research, 2023)
The paper investigated the effect of foreign exchange market liquidity on exchange rate. Its objective is to determine the causal relationship between foreign exchange market liquidity and exchange rate.. While there is a relationship between foreign exchange market liquidity and the currency rate, the direction of such relationship is yet to be ascertained in both magnitude and size in Nigeria within the period under review. The secondary data were sourced from various issues of Central Bank of Nigeria Statistical Bulletin. Result indicated that there is a unidirectional causality between foreign exchange market liquidity and exchange rate. This implies that the foreign exchange market liquidity does not drive currency exchange rate in Nigeria hence foreign exchange market is not as liquid as it is always thought. Furthermore, foreign exchange liquidity is tied to the general market. It is not as independent as it is viewed to be. Its liquidity is also dependent on the liquidity of various classes of assets such as equity, bonds and others. This suggested that liquidity shocks are a cross-market phenomenon and not limited to the foreign exchange market only. The paper recommended that the monetary authorities should put in place exchange rate policy that will engender liquidity of the FEM. There is need to match the demand and supply of foreign exchange. The rate of inflation should be monitored to allow desirable rate that will engender liquidity in the foreign exchange market while efforts to restore confidence in the Naira should be pursued.